Biomedical applications of polymer and ceramic coatings: a review of recent developments. (2nd January 2022) - Smith, J. R.; Lamprou, D. A.; Larson, C.; Upson, S. J.
ABSTRACT: Recent literature concerning the use of polymer and ceramic coatings for a variety of biomedical applications is surveyed in this review. Applications have been grouped into six broad categories: orthopaedic materials, cardiovascular stents, antibacterial surfaces, drug delivery, tissue engineering and biosensors. Polymer and ceramic coatings add enhanced corrosion protection, antiwear, antibacterial and biocompatibility properties to various substrates for biomedical applications. Processes favoured for polymer coating formation included dip, electrodeposition, spin (including electrospin) and spray (including electrospray and ultrasonic spray). Ceramic coatings were formed using magnetron sputtering and a combination of 3-D printing and in-situ mineralisation, among others. The review period is from 2017 to the present (mid-2021).